Identification and postnatal developmental characteristics of brown adipose tissue in yak calves - Chen Fuju; Zhao Yutian; Ling Xiaodong (Veterinary Medicine and Science, 2024)
Abstract Background Brown adipose tissue (BAT) provides newborn mammals with a critical capacity for non‐shivering thermogenesis and enables their adaptation to the cold of the extrauterine environment. The domestic yak (Bos grunniens) has evolved on the Qinghai–Tibet Plateau and has adapted well to extremely cold and hypoxic environments. However, the location, characterization and postnatal development of BAT in yak calves remain largely unknown. Methods We identified different types of adipocytes and explored the postnatal development of interscapular and subcutaneous adipose tissue in yak calves at 1, 7 and 30 days old using morphological and molecular biology methods. Results The results show that multilocular and unilocular adipocytes were found in two depots. Multilocular adipocytes contained small lipid droplets packed with numerous mitochondria. However, unilocular adipocytes contained a single unilocular lipid droplet and few mitochondria. The number of multilocular adipocytes significantly decreased, whereas the number of unilocular adipocytes significantly increased from day 1 to 30. Furthermore, uncoupling protein 1 (UCP1) expressions in both multilocular and unilocular adipocytes, as well as UCP1 mRNA and protein expression, were significantly decreased from day 1 to 30. In addition, peroxisome proliferator‐activated receptor‐γ coactivator‐1α and peroxisome proliferator‐activated receptor alpha mRNA expression were significantly decreased. Conclusions The results of the research indicate that adipocytes in both newborn yak calf interscapular and subcutaneous adipose tissue are multilocular adipocytes. Many multilocular adipocytes were transformed into unilocular adipocytes after birth, but some multilocular adipocytes remained at day 30; this transition occurred at different rates in different depots. These results provide a basis for further study of BAT in yak calves.